2008
DOI: 10.1111/j.1399-6576.2008.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcome in ICU‐acquired infections

Abstract: Mortality was increased by ICU-acquired pneumonia and primary bloodstream infections. Our findings did not support the gastro-pulmonary hypothesis of ICU-acquired pneumonia. The proposition that blood transfusions increase the risk of ICU-acquired nosocomial infections was not supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
4
11
2
3
Order By: Relevance
“…Conversely to our results, many previous studies have shown that greater illness severity on ICUadmission, expressed with APACHE II or APACHE III score, is related to the higher risk of developing ICU-BSI [13,[32][33][34]. The finding of a negative relationship between APACHE II minus age points at ICUadmission, and the development of ICU-BSI in our study, suggests a high rate of early mortality among critically ill patients with domicile infections, which has lowered their chance for development of ICU-BSI.…”
Section: Variablescontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely to our results, many previous studies have shown that greater illness severity on ICUadmission, expressed with APACHE II or APACHE III score, is related to the higher risk of developing ICU-BSI [13,[32][33][34]. The finding of a negative relationship between APACHE II minus age points at ICUadmission, and the development of ICU-BSI in our study, suggests a high rate of early mortality among critically ill patients with domicile infections, which has lowered their chance for development of ICU-BSI.…”
Section: Variablescontrasting
confidence: 99%
“…Due to longer use of ICU facilities (CVC, MV and ICU stay) in our patients, the observed overall ICU-BSI rate of 26.1% in elderly and 21.1% in younger adults were much higher in comparison to those reported from other studies, which ranged between 2.7-9.0% [15,19,33,[35][36][37]. Relatively expressed ICU-BSI incidence of 12.4 ICU-BSIs in elderly and 12.3 in younger adults per 1,000 ICU days in our observed severe infectious disease patients fits among the results of other studies, where that incidence in patients treated at ICU, because of different medical and surgical conditions, was mostly in the range of 5-19/1,000 ICU days [19,35,37].…”
Section: Variablescontrasting
confidence: 61%
“…Moreover, candidemia in the ICU is by far more common than in most other wards and can affect up to about 10% of all admitted patients [18,19]. Additionally, Candida species account for approximately 3% of all surgery-related peritoneal infections, both community-acquired infections and nosocomial infections [20].…”
Section: Epidemiology Of Invasive Candidiasismentioning
confidence: 99%
“…BSI is more common in patients who have surgery, are immunocompromised, develop multiorgan dysfunction, require mechanical ventilation or renal replacement therapy, and have greater illness severity on ICU admission [3,20,21]. Some critically ill patients may be genetically predisposed to both developing BSI and dying in hospital [22].…”
Section: Introductionmentioning
confidence: 99%